2024
DOI: 10.3389/fonc.2024.1303335
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of CTC, ctDNA, and EVs in cancer liquid biopsy

Xiaoling Wang,
Lijuan Wang,
Haihong Lin
et al.

Abstract: Circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and extracellular vehicles (EVs) have received significant attention in recent times as emerging biomarkers and subjects of transformational studies. The three main branches of liquid biopsy have evolved from the three primary tumor liquid biopsy detection targets—CTC, ctDNA, and EVs—each with distinct benefits. CTCs are derived from circulating cancer cells from the original tumor or metastases and may display global features of the tumor. ctDNA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 231 publications
0
1
0
Order By: Relevance
“…After tracking the expression of CD31, we found that rTor-LIP promoted renal angiogenesis in AKI animals, and it also reduced the degree of apoptosis in renal functional cells as found by the TUNNEL assay. It is well known that fibrosis can lead to organ structural damage and dysfunction, even failure, which threatens human health and life ( Liu et al, 2022 ; Wang et al, 2024 ). Fibrosis is mainly characterized by the increase of fibrous connective tissue in organ tissues ( Rane et al, 2019 ; Bai and Liu, 2021 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After tracking the expression of CD31, we found that rTor-LIP promoted renal angiogenesis in AKI animals, and it also reduced the degree of apoptosis in renal functional cells as found by the TUNNEL assay. It is well known that fibrosis can lead to organ structural damage and dysfunction, even failure, which threatens human health and life ( Liu et al, 2022 ; Wang et al, 2024 ). Fibrosis is mainly characterized by the increase of fibrous connective tissue in organ tissues ( Rane et al, 2019 ; Bai and Liu, 2021 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%